MetBil as a novel molecular regulator in ischemia‐induced cardiac fibrosis via METTL3‐mediated m6A modification. Issue 3 (8th February 2023) - Zhuang, Yuting; Li, Tingting; Hu, Xiaoxi; Xie, Yilin; Pei, Xinyu; Wang, Chaoqun; Li, Yuyang; Liu, Junwu; Tian, Zhongrui; Zhang, Xiaowen; Peng, Lili; Meng, Bo; et al.
Abstract: Cardiac fibrosis is a common pathological manifestation in multiple cardiovascular diseases and often results in myocardial stiffness and cardiac dysfunctions. LncRNA (long noncoding RNA) participates in a number of pathophysiological processes. However, its role in cardiac fibrosis remains unclear. The purpose of this study was to investigate the role and molecular mechanism of MetBil in regulating cardiac fibrosis. Our data showed that METTL3 binding lncRNA (MetBil) was significantly increased both in fibrotic tissue following myocardial infarction (MI) in mice and in cardiac fibroblasts (CFs) exposed to TGF‐β1 (20 ng/mL) or 20% FBS. Overexpression of MetBil augmented collagen deposition, CF proliferation and activation while silencing MetBil exhibited the opposite effects. Importantly, heterozygous knockout of MetBil alleviated cardiac fibrosis and improved cardiac function after MI. RNA pull‐down and RNA‐binding protein immunoprecipitation assay showed that METTL3 is a direct downstream target of MetBil; consistently, MetBil and METTL3 were co‐localized in both the nucleus and cytoplasm of CFs. Interestingly, MetBil regulated METTL3 expression at protein level, but not mRNA level, in ubiquitin–proteasome pathway. Enforced expression of METTL3 canceled the antifibrotic effects of silencing MetBil reflected by increased collagen production, CF proliferation and activation. Most notably, the m6A‐modified fibrosis‐regulated genes mediated by METTL3 are profoundly involved in the regulation of MetBil in the cardiac fibrosis following MI. Our study reveals that MetBil as a novel regulator of fibrosis promotes cardiac fibrosis via interacting with METTL3 and regulating the expression of the methylated fibrosis‐associated genes, providing a new intervening target for fibrosis‐associated cardiac diseases. Abstract : Our study showed that overexpression of MetBil augmented collagen deposition, cardiac fibroblast proliferation and activation while silencing MetBil exhibited the opposite effects. Heterozygous knockout of MetBil alleviated cardiac fibrosis and improved cardiac function after myocardial infarction. MetBil binding protected METTL3 from ubiquitin modification and promoted METTL3‐mediated m6A modification and expression of fibrosis‐associated genes, therefore resulting in cardiac fibrosis.